Peran Teknologi Informasi Dan Komunikasi Dalam Pendidikan - Budiman, Haris (Universitas Islam Negeri Raden Intan Lampung, 2017)
This study aims to determine the role of information and communication technology in education. The information and communication technology in general aims to make students understand information and communication technology devices in general, including computers (literacy) and information literacy, which means students recognize the terms used in information and communication technology. In the Qur'an there are so many commands, statements, suggestions, satires and so on that substantially link Islamic teachings to science and technology. The results of this study found that the role of information technology in education, in addition to helping students in learning also had a quite influential role for teachers, especially in the use of facilities to enrich teaching skills, and the Qur'an as a guide and guidance for the development of science and technology in order to strengthen faith and improve human well-being.